Changes in Self-Reported Concussion History after Administration of a Novel Concussion History Questionnaire in Collegiate Recreational Student-Athletes - Adam Copp; Monica R. Lininger; Meghan Warren (MDPI AG, 2017)
Research has shown that exposure to a concussion definition (CD) increases self-reported concussion history (SRCH) immediately, however, no research has been performed that examines the effects of exposure to a CD on SRCH over time. Collegiate recreational student-athletes (RSAs) have limited access to monitoring and supervision by medical staff. As such, recognition of concussion symptoms and need for medical management oftentimes falls upon the RSA. The purpose of this study was to assess the effect of a novel questionnaire on the SRCH of RSAs. A two-part questionnaire was sent to RSAs participating is sports with a greater than average risk of concussion at a university in Arizona. Data from 171 RSAs were analyzed to assess the change in RSAs' suspected concussion estimates pre- and post-exposure to a CD and concussion symptom worksheet, as well as over the short-term (2.5 months). Approximately one-third of RSAs reported an increase in suspected concussion estimates immediately following exposure to the questionnaire, but the change was not maintained over the short-term. The results suggest that a single exposure to a CD is ineffective at increasing short-term SRCH estimates.